Improving quality of care and timely access to radiation therapy for patients with invasive cervical cancer at the National Cancer Institute Paraguay - Geraldine Jacobson; Linus Chuang; Maximilian Pankow (Elsevier, 2018)
The purpose of this report is to describe the interventions implemented between 2012 and 2017 at the National Cancer Institute Paraguay (NCI Paraguay) to improve treatment quality and efficiency for patients with cervical cancer, with an emphasis on radiation quality and access. The NCI Paraguay requested collaboration with Health Volunteers Overseas (HVO), an international volunteer organization, to improve the care of patients with cervical cancer. This report is based on site visits to NCI Paraguay by HVO volunteers in 2012, 2013, and 2016, with a follow-up report from the site in 2017. During the study period, increased access to external beam radiation and brachytherapy led to a decrease in wait time to start radiation from 2 to 3 months to 4-6 weeks. The center transitioned from 2-dimensional (2D) to 3-D planning and was able to offer concurrent chemotherapy and radiation, including brachytherapy, to patients with locally advanced cervical cancer. Based on the American Society of Clinical Oncology's resource-stratified clinical guidelines, from 2012 to 2017, the practice transitioned from a "basic setting" to an "enhanced setting". Keywords: Cervical cancer, Radiation therapy, Paraguay, Low- and middle-income countries, ASCO resource-stratified clinical practice guidelines